Control in Subsidiary Networks in Asia: Toward an Extension of the Centralisation-Formalisation-Socialisation (CFS) Model - Amann, Bruno; Jaussaud, Jacques; Schaaper, Johannes (Management international / International Management / Gestiòn Internacional, 2017)
Prior research establishes that international control by multinational corporations is based on three dimensions: centralisation, formalisation and socialisation. New control mechanisms appeared in the last decade, such as enterprise resource planning, short-term assignments and regional centres. Do these new mechanisms fit the three control dimensions? How do MNCs articulate their control mechanisms, including new ones? Using interviews with 77 managers of 47 French MNCs in 11 Asian countries, this study presents an exploratory factor analysis and clustering. The findings show that French MNCs control their Asian subsidiaries through four dimensions: centralisation of decision making, formalisation of subsidiaries, socialisation and expatriation.